A Traffic Accident which Causes Atypic Traumatization in the Shape of Garotte at the Collum Case Report - Türkoğlu, Abdurrahim; Tokdemir, Mehmet; Tunçez, Ferhat Turgut; Börk, Turgay (The Bulletin of Legal Medicine, 2011)
Death as a result of traffic accidents is of importance in terms of judicial conditions, and the cause of death has to be clarified. Certain atypical lesions may occur in deaths caused by traffic accidents, and the evaluation of these lesions leads a number of difficulties during post mortem examination. Many factors such as the type and speed of vehicle, and the security measures of vehicle during the accident, are involved in the occurrence of the lesions. The importance of factors which are remarkable at the differential diagnosis of the findings, which show similarity with lesions which may occur as a result of throat cut with a sharp object, as is detected in presented case, has been discussed. Our case is a 70-year-old male who died at the scene after a traffic accident. The autopsy performed at Firat University Medical Faculty, Department of Forensic Medicine revealed an 8x3 cm neck injury -above the thyroid cartilage- with partly irregular wound margins involving complete dissection of left vena jugulari s i ntema, left arteria tiroidea superior, neck veins, together with neck structures as esophagus and the trachea, soft tissues and muscles. It was observed during the examination of the pictures of the scene of accident that, the passenger who sat on the right seat in front of the windscreen had a roundshaped fracture on his head, which had occurred because his head skidded. Atypical injuries might occur in traffic accidents. Forensic Medicine experts sometimes face various difficulties while evaluating such injuries. In this regard, pre-autopsy evaluation of findings of accident scene investigation by Forensic Medicine specialist will contribute solving cases.Key words : Traffic accident, investigation at the accident scene, forensic medicine
Keywords: traffic accident; investigation at the accident scene; forensic medicine